When one business model is not enough for a social business. Issue 1 (9th January 2017) - Gebauer, Heiko; Saul, Caroline; Halidmann, Mirella; Kramer, Sasha
Abstract : Purpose: This paper aims to illustrate how managing multiple business models can become a key factor for succeeding in base-of-the-pyramid markets. Design/methodology/approach: Case study was conducted through an engaged scholarship approach. Findings: The authors highlight that companies can manage multiple business models, if they are following these three steps: recognition of costs-and-benefits, improvement and growth and creation of synergies. Practical implications: The study provides guidance on how to manage multiple business models. Social implications: This paper discusses Sustainable Organic Integrated Livelihoods, a social enterprise, which provides basic sanitation in bade-of-the-pyramid markets. Originality/value: Operating more than one business model could cause often strategic failures. Sustainable Organic Integrated Livelihoods explored the advantages of having multiple business models in following three steps: recognition of costs-and-benefits, improvement and growth and creation of synergies.